Design-based research in designing the model for educating simulation facilitators. (March 2018) - Koivisto, Jaana-Maija; Hannula, Leena; Bøje, Rikke Buus; Prescott, Stephen; Bland, Andrew; Rekola, Leena; Haho, Päivi
Abstract: The purpose of this article is to introduce the concept of design-based research, its appropriateness in creating education-based models, and to describe the process of developing such a model. The model was designed as part of the Nurse Educator Simulation based learning project, funded by the EU's Lifelong Learning program (2013-1-DK1-LEO05-07053). The project partners were VIA University College, Denmark, the University of Huddersfield, UK and Metropolia University of Applied Sciences, Finland. As an outcome of the development process, "the NESTLED model for educating simulation facilitators" (NESTLED model) was generated. This article also illustrates five design principles that could be applied to other pedagogies. Highlights: There is a need to develop educator competency to facilitate simulation-based learning in nurse education exists. Design-Based Research project facilitated the generation of the NESTLED model and five reusable design principles. The NESTLED model for educating simulation facilitators was developed through iterative design cycles. The project was conducted in close collaboration amongst researchers and simulation facilitators from three countries.